Egg Quality Traits of Layers Influenced by Supplementation of Different Levels of Sugarcane Press Residue - Suma, N.; Reddy, B.S. Venkatarami; Doss, R. G. Glori; Rao, Rajeswara; Singh, K. Chandrapal; Rekha, M.T.; Gomes, Amitha R. (International Journal of Poultry Science, 2007)
Nearly three percent of the crushed sugarcane from sugar industries turns into Sugarcane Press Residue (SPR), which is a valuable source of minerals as well as organic matter. A biological experiment was conducted using 160 (32-week old) white leg horn hens to assess the beneficial effect of Sugarcane Press Residue (SPR) in soya and fish based diets. Two BIS (1992) specified practical control diets for both soya (T1) and fish based (T5) test diets were formulated, while the SPR was included at three levels (5%, 10% and 15%) in test diets of both soya based (T2 to T4) and fish based (T6 to T8) types to form a total of eight treatment diets. Each of such formulated diets was offered to five replicates of four birds each reared in colony cages for a period of twelve weeks. Among the egg characteristics studied, the 84 day mean egg weights were found to be 54.70, 53.58, 52.46, 54.69, 54.09, 54.22, 53.21 and 52.62 g in T1 through T8 groups, respectively. Inclusion of SPR inconsistently (p>0.05) reduced the egg weights when compared to control groups both in soya and fish based diets. Average egg shape index values ranged from 76.30 (T1) to 78.16 (T7). Mean albumen index values were comparable. Mean Haugh unit score values ranged (p>0.05) from 52.17 (T1) to 56.49 (T8). From the different egg parameters studied, it can be concluded that SPR appears to be a valuable source of organic as well as inorganic nutrients for economical layer production.